The Practical Preparation of Chiral N-Sulfonyl Oxaziridines via Catalytic Asymmetric Payne Oxidation - Tsutsumi, Ryosuke; Kim, Seonwoo; Uraguchi, Daisuke; Ooi, Takashi (Synthesis, 2014)
The asymmetric Payne oxidation of N-sulfonyl imines catalyzed by a P-spiro chiral triaminoiminophosphorane was developed for the practical synthesis of optically active N-sulfonyl oxaziridines. High efficiency and an excellent level of enantioselectivity were generally achieved with a wide variety of aldimines by choosing appropriate reaction conditions. The versatility of this method was demonstrated by the diastereoselective kinetic oxidation of racemic α-chiral N-sulfonyl imines.
Keywords: asymmetric catalysis; oxaziridines; oxidation; peroxides; stereoselective synthesis